Review of Obstetrical Emergencies: Its Concept and Optimal Management - Simarjeet Kaur; Poonam Sheoran; Jyoti Sarin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Obstetrical emergencies are life threatening conditions that occur in pregnancy during labour and after delivery. It is common that approximately 15% of all pregnant women develop serious complication from conception to delivery. Obstetrical emergencies may turn catastrophic in women, so every little contribution to save maternal and neonatal life brings about reduction in maternal and neonatal mortality and morbidity. Among all the emergency situations which may arise across the field of obstetrics, there are small numbers which call urgent practical steps to be taken in order to safeguard the life of the mother or the baby or both. Emergency obstetric care is a set of critical lifesaving functions commonly called signal functions provided by a health care facility throughout the day and week. Obstetric complications can neither be predicted nor be prevented but can be managed by timely provision of life saving services. When obstetric emergencies occur, effective and efficient care by the health care professionals is essential for good outcome and safety. Diagnosis of serious situation to delivery interval should be less than 30 minutes; however, it is expected to be lengthy then appropriate measure should be taken to manage the obstetric complications. Prompt diagnosis , timely performed intervention and positive impact of maternal and neonatal management have significantly improved the maternal and neonatal outcome.